Images of the Prophet Muhammad in English Literature: By Abdur Raheem Kidwai (New York: Peter Lang, 2018. 168 pages.) (American Journal of Islam and Society, 2019)
‘Literary Orientalism’, a significant and fast-emerging sub-genre, is simply defined as “the study of the (mis)representation of Islam and Muslims in the English (literary) works.” In this field, one of the prominent Muslim writers from India is Abdur Raheem Kidwai (Professor of English, and Director, K.A. Nizami Centre for Quranic Studies, Aligarh Muslim University, India). Some of his previous works in this genre include Orientalism in Lord Byron’s Turkish Tales (1995); The Crescent and the Cross (1997); Stranger than Fiction (2000); Literary Orientalism (2009); Believing and Belonging (2016); and Orientalism in English Literature (2016).To download full review, click on PDF.